The legal vacuum of the actions protecting the right of information in Ecuador - Jácome, Josselyn; Meythaler, Beatriz (USFQ Law Review, 2015)
In Ecuador, the right of access to information is protected through two constitutional mechanisms, habeas data, and access to public information. Although the goal of each action is to protect the right of access to the information, content and scope of each one of those actions is different. While habeas data allows the access to personal information, the action of access to public information allows counting the society in the work of the Public Administration. However, as we will discuss in subsequent lines, there are cases in which access to the information of a missing or deceased person is an impossible task, especially when it comes to personal data or facts surrounding the situation of your destination. For this reason, this essay has a purpose study the scope of the constitutional action of access to public information and habeas data, then check the limitations to the right of information and how this affects the right of access to information and the right to the truth of the family of the deceased or of the disappeared. After understanding the limitations of these actions, we are going to verify the existence of the legal vacuum that may be incurred and its possible solution.
Keywords: Access to information; public information; habeas data; right to privacy; legal limitations; legitimacy; right to the truth; missing persons or deceased persons